IMPLEMENTATION OF HOTS-BASED LEARNING AND PROBLEM BASED LEARNING DURING THE PANDEMIC OF COVID-19 IN SMA BUDI MULIA JAKARTA - Murniarti, Erni; Sirait, Sarwedi; Sihotang, Hotmaulina (Advances in Social Sciences Research Journal, 2021)
The implementation of the 2013 curriculum requires teachers to change their views in implementing learning process in schools. Learning strategies are no longer teacher-centered learning but learner-centered learning. Teachers are required to organize creative and innovative learning as stated in the Lesson Plan. Teachers must master various methods to improve higher-order thinking skills (HOTS) of students. In this context, Problem Based Learning (PBL) is the appropriate model in developing students' thinking skills. The 2013 curriculum has adopted Bloom's taxonomy which was revised by Anderson starting from the level of knowing, understanding, implementing, analyzing, evaluating and creating. Because the demands of the 2013 Curriculum must be at the level of creating, students must be continuously trained to produce something new. This study aims to describe the Problem Based Learning (PBL) learning method as a model of effective way to build critical and creative thinking skills of students at SMA Budi Mulia Jakarta. This study also explains HOTS-based assessment as a logical assessment of PBL learning.